The influence of triiodothyronine (T-3) on the early development of piracanjuba (Brycon orbignyanus) - Landines, M. A.; Sanabria, A. I.; Senhorini, J. A.; Urbinati, Elisabeth Criscuolo [UNESP] (Springer, 2010)
This paper reports the triiodothyronine's (T-3) effects on the early growth and survival of piracanjuba (Brycon orbignyanus) produced from fertilized eggs hormone exposed The study was carried out in two phases In the first phase, eggs divided in 6 batches were Immersed in T-3 solutions 0 01, 0 05, 0 1, 0 5 ppm, 1 ppm and control (no T-3) After a 15-min immersion, eggs were transferred to incubators where larvae were kept up to 72 h after hatching Larval weight, length and yolk sac volume were determined every 12 h Sixty and 72 h after hatching, larvae exposed to 0 5 ppm T-3 were significantly heavier than the others, and those exposed to 1 ppm T-3 showed the lowest weight The yolk sac absorption was not affected In the second experimental phase, the resulting fry from the first phase were stocked into 3 boxes per treatment (5 larvae L-1) and fed with plankton, fish larvae and feed prepared in the hatchery (48% CP) in the first 3 days, plankton and feed from the 4th to the 10th day and only feed in the next (last) 5 days Fry weight, length and specific growth rate were determined at 1, 5, 10 and 15 days Survival was calculated in the last day In the 15th day, fry length did not differ among treatments but the weight of the control group was higher Higher survival in the T-3-treated groups suggested lower predation among fry The results allowed us to conclude that there was no expressive effect of T-3 on the growth, but it improved the survival of the piracanjuba progeny
Keywords: Growth; Larvae; Survival; Thyroid hormone